Coleridge and Column Inches - Hessell, Nikki (Romanticism on the Net, 2005)
AbstractBuilding on research by David Erdman, this essay seeks to re-examine Coleridge’s parliamentary reports of 1800 within the context of contemporary reporting practices. A comparison of Coleridge’s accounts of his trips to the House of Commons with standard accounts of parliamentary reporting and its norms shows that Coleridge was given special license by the editor of the Morning Post, Daniel Stuart. While David Erdman focused on the length and accuracy of the reports as a basis for his claim that Coleridge was a superior parliamentary correspondent, this essay argues that it is the space granted to Coleridge’s reports in the Morning Post and the freedom he was afforded as a journalist that demonstrates the importance of his contributions to parliamentary coverage.